Vertical Movements of Juvenile Sablefish in Coastal Southeast Alaska. Issue 1 (1st January 2017) - Coutré, Karson M.; Beaudreau, Anne H.; Courtney, Dean; Mueter, Franz J.; Malecha, Patrick W.; Rutecki, Tom L.
Abstract: Diel vertical migration is commonly associated with pelagic fish species, but demersal fishes may also undertake vertical movements while managing foraging tradeoffs during their vulnerable juvenile stage. We examined fine-scale vertical movements of age-0 juvenile Sablefish Anoplopoma fimbria to better understand behavioral patterns that may affect their survival in nearshore habitats. Thirteen juvenile Sablefish (mean FL = 241.9 mm) were implanted with acoustic transmitters and were monitored by use of two acoustic receivers from October 5 to November 14, 2003, within St. John Baptist Bay, Baranof Island, Alaska. The six fish that remained within range of the receivers spent the majority of their time near the bottom but made periodic vertical excursions. Generalized linear mixed-effects models were used to determine the relationships between excursion frequency and the tidal stage and diel period. For all Sablefish, variation in excursion frequency was related to date and diel period, with the highest excursion frequency observed during dawn and day periods and the lowest frequency observed at night. Over the 40-d period, excursion frequency increased to a peak on day 33 (i.e., early November). Generalized linear models for each individual fish supported the finding that the excursion behavior was primarily related to date and diel period; however, tidal stage also explained variation in excursion frequency for three of the six individuals that remained within receiver range. This study is the first to describe vertical migration of juvenile Sablefish in the wild and reveals that environmental conditions have the potential to influence the fine-scale movements of juvenile Sablefish within nearshore habitats. Received June 12, 2016; accepted January 13, 2017